Jaguars in Corcovado National Park, Costa Rica - Sarmiento, Rausel (2007)
The population size estimations of the jaguar (Panthera onca) were compared, derived from two sessions of sampling and a previous work, the three sessions obtained in the 2003, in the central part of the Corcovado National Park (PNC), Costa Rica. Was used the cameras trap technique and models of closed population. The comparison of the populations size indicated that these technique is efficient in the dry season. The population size estimations obtained under a conservative scenario and an ideal scenario alert on the necessity to take care of the quality of the habitat into de PNC and those outside in order to assure the individuals flow, otherwise are few the probabilities of long term subsistence of this specie.